Hemoglobin screening: response of a Brazilian community to optional programs Triagem de hemoglobinopatias: resposta de uma comunidade brasileira a programas opcionais - Antonio Sérgio Ramalho; Roberto Benedito de Paiva e Silva; Rosa Chelminsky Teixeira; Mariane Bernadete Compri (Cadernos de Saúde Pública, 1999)
The efficiency and the viability of three hemoglobin screening programs were investigated. They were offered on a voluntary basis to a Brazilian population and started with the analysis of blood donors, pregnant women and students. The hemoglobin screening was done through optional exams which included electrophoresis of hemoglobin and complementary hematological tests. A total of 13,670 people were tested over a period of 39 months and a total of 644 individuals with hereditary hemoglobin disorders were detected - 4.7% of the samples examined. The programs showed satisfactory indicators of viability and efficiency, expressed by the significative proportion of exams performed among the probands and their relatives. Foram testadas a viabilidade e a eficiência de três programas de triagem de hemoglobinopatias. Os programas foram oferecidos voluntariamente a uma população brasileira e iniciaram com o exame de doadores de sangue, gestantes e escolares dos ensinos fundamental e médio. A triagem das hemoglobinopatias foi realizada mediante exames opcionais, representados pela eletroforese de hemoglobinas e exames complementares. Um total de 13.670 pessoas foram investigadas em um período de 39 meses, diagnosticando-se 644 portadores de alterações hereditárias da hemoglobina - 4,7% da amostra examinada. Os programas mostraram indicadores satisfatórios de viabilidade e de eficiência, expressos pela proporção significativa de exames realizados entre os propósitos e os seus parentes.